2009
DOI: 10.4238/vol8-3gmr603
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms from Theobroma cacao expressed sequence tags associated with witches’ broom disease in cacao

Abstract: ABSTRACT. In order to increase the efficiency of cacao tree resistance to witches' broom disease, which is caused by Moniliophthora perniciosa (Tricholomataceae), we looked for molecular markers that could help in the selection of resistant cacao genotypes. Among the different markers useful for developing marker-assisted selection, single nucleotide polymorphisms (SNPs) constitute the most common type of sequence difference between alleles and can be easily detected by in silico analysis from expressed sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
(15 reference statements)
0
9
1
3
Order By: Relevance
“…High frequency or no SNP was found in the ORF and in the 5'UTR (untrans-lated region), low frequency or no SNP was observed in the 3'UTR, in the four genes in which the SNPs were validated, as follows: Disease resistance protein (46% in ORF, 54% in 5'UTR), â-1,3-glucanase (10% in ORF, 40% in 5'UTR, 50% in 3'UTR), Phenylalanine ammonia lyase (25% in ORF, 42% in 5'UTR, 33% in 3'UTR), and Pathogenesis related protein (92% in ORF, 8% in 5'UTR). The presence of a great amount of SNPs in ORFs was unexpected and contradicted previous works showing that the UTRs have a higher frequency of SNPs than the rest of the genome (Zhu et al 2001;Ching et al 2002), but agrees with Lima et al (2009) work, in which SNPs were found more frequently in the ORF (44%) and in the 5'UTR (untranslated region) (32%) than in the 3'UTR. The condition of forward sequencing may explain the low frequency or absence of SNPs in the 3'UTR; the 5'UTR was sequenced, and the 3'UTR was, either partially sequenced or not sequenced depending on the length of the ORF, making it difficult to detect SNPs in this region.…”
Section: Resultscontrasting
confidence: 44%
See 2 more Smart Citations
“…High frequency or no SNP was found in the ORF and in the 5'UTR (untrans-lated region), low frequency or no SNP was observed in the 3'UTR, in the four genes in which the SNPs were validated, as follows: Disease resistance protein (46% in ORF, 54% in 5'UTR), â-1,3-glucanase (10% in ORF, 40% in 5'UTR, 50% in 3'UTR), Phenylalanine ammonia lyase (25% in ORF, 42% in 5'UTR, 33% in 3'UTR), and Pathogenesis related protein (92% in ORF, 8% in 5'UTR). The presence of a great amount of SNPs in ORFs was unexpected and contradicted previous works showing that the UTRs have a higher frequency of SNPs than the rest of the genome (Zhu et al 2001;Ching et al 2002), but agrees with Lima et al (2009) work, in which SNPs were found more frequently in the ORF (44%) and in the 5'UTR (untranslated region) (32%) than in the 3'UTR. The condition of forward sequencing may explain the low frequency or absence of SNPs in the 3'UTR; the 5'UTR was sequenced, and the 3'UTR was, either partially sequenced or not sequenced depending on the length of the ORF, making it difficult to detect SNPs in this region.…”
Section: Resultscontrasting
confidence: 44%
“…Similar high frequency of SNPs has been found in other crops, for example in maize wherein 1 SNP per 31 bp in non-coding region and 1 SNP per 124 bp in the coding region, these were obtained based on the analysis of 18 genes in 36 inbred lines . Lima et al (2009) (Table 2). Substitutions in the coding region that lead to alterations in the amino acid sequences and/or early termination of the translation process may cause an altered phenotype (Klug et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 SNP/63 bp and 1 SNP/130 bp in Pinus taeda and Populus trichocarpa, respectively; Brown et al 2004;Gilchrist et al 2006). However, information is Lima et al 2009). Grape is an exception as its SNP frequency has been estimated in various studies as 1 SNP/117 bp (based on the Pinot Noir genome sequence; Velasco et al 2007) or 1 SNP/64-104 bp (based on multi-locus analysis of cultivars; Lijavetzky et al 2007;Vezzulli et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…With the exception of Brazil and Malaysia, most cacao breeding is carried out in countries where it has been technically difficult to use microsatellite markers, requiring the majority of the genotyping to be done in the USA, France, or Great Britain. For the last 10 years, we, and others, have been developing and applying molecular markers for use in breeding improved cacao (T. cacao) varieties and curating the world's germplasm resources of cacao (Kuhn et al 2003(Kuhn et al , 2006Borrone et al 2004Borrone et al , 2007Schnell et al 2007; Motilal and Butler 2003;Zhang et al 2009;Motilal et al 2010;Irish et al 2010;Risterucci et al 2000;Pugh et al 2004;Lima et al 2009). Currently, a single-nucleotide polymorphism (SNP) assay we developed is being used in breeding efforts in Ghana and is also being established in Cote d'Ivoire (Livingstone et al 2011), the two top cocoa-producing countries in the world.…”
Section: Introductionmentioning
confidence: 99%